1997
DOI: 10.1071/ea96137
|View full text |Cite
|
Sign up to set email alerts
|

Biological studies of soils in paired old and new land sites growing sugarcane

Abstract: Summary. The growth of sugarcane in soils from land monocultured with sugarcane, and from land which had either never been cropped with sugarcane, or just recently cropped, was compared under glasshouse conditions. In general, cane growth in new land soils was greater than in monocultured soil (shoot growth 7.4%, root growth 21.4%). Responses to soil pasteurisation were investigated in some soils and were greater in monocultured soils suggesting that root growth constraints were larger in the monocultured soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Enzymes activities have been suggested as sensitive indicators of soil biological properties (Dick, 1997;Nannipieri, 1994). The literature assessed showed that natural habitats have the highest enzymes' activity followed by pasture, while sugarcane presented a low enzymes' activity (Cardoso et al, 2016;Brackin et al, 2013;Ye and Wright, 2010;Sant'Anna et al, 2009;Zou and Bashkin, 1998;Magarey et al, 1997).…”
Section: Soil Biological Propertiesmentioning
confidence: 99%
“…Enzymes activities have been suggested as sensitive indicators of soil biological properties (Dick, 1997;Nannipieri, 1994). The literature assessed showed that natural habitats have the highest enzymes' activity followed by pasture, while sugarcane presented a low enzymes' activity (Cardoso et al, 2016;Brackin et al, 2013;Ye and Wright, 2010;Sant'Anna et al, 2009;Zou and Bashkin, 1998;Magarey et al, 1997).…”
Section: Soil Biological Propertiesmentioning
confidence: 99%